2012
DOI: 10.1093/bja/aes314
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging study of the in vivo position of the extraglottic airway devices i-gel™ and LMA-Supreme™ in anaesthetized human volunteers

Abstract: The LMA-S and i-gel™ differ significantly with regard to in situ position and spatial relationship with adjacent structures assessed by MRI, despite similar clinical and fibreoptical findings. This could be relevant with regard to risk of aspiration, glottic narrowing, and airway resistance and soft-tissue morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 24 publications
2
37
0
6
Order By: Relevance
“…In a study with volunteers, Russo et al found that the LMA Supreme protrudes deeper into the upper esophageal sphincter than the i-gel despite fibreoptically identical positions and more compression of the laryngeal inlet by the LMA-Supreme than by the i-gel. 11 Our study suggests that both devices have similar successful insertion rates and equivalent leak and peak inspiratory pressures. These findings are in agreement with those of previous reports.…”
Section: Discussionsupporting
confidence: 50%
“…In a study with volunteers, Russo et al found that the LMA Supreme protrudes deeper into the upper esophageal sphincter than the i-gel despite fibreoptically identical positions and more compression of the laryngeal inlet by the LMA-Supreme than by the i-gel. 11 Our study suggests that both devices have similar successful insertion rates and equivalent leak and peak inspiratory pressures. These findings are in agreement with those of previous reports.…”
Section: Discussionsupporting
confidence: 50%
“…This seal is referred to as hypopharyngeal seal pressure (HLP) or 'second seal' (Fig. 1, from [6]). The seal formed with the upper oesophageal sphincter must be effective in both directions, that is, it must protect against gastric insufflation with positive pressure ventilation while also preventing the movement of stomach contents into the respiratory tract in case of regurgitation [7].…”
Section: Second-generation Supraglottic Airwaysmentioning
confidence: 99%
“…The cause is thought to be the flattened tip of the i-gel that is possibly not inserted far enough into the postcricoid region [6]. The HLP is thus dependent on the particular design of the SGA as well as its correct positioning.…”
Section: Key Pointsmentioning
confidence: 99%
“…Le LMA-Suprême TM semble provoquer plus de fermetures que les autres modè les, à la fois dans l'é tude de Seet et al [2] et dans notre é tude. Une des raisons possibles est la forme du dispositif qui place son extré mité au niveau du sphincter supé rieur de l'oesophage [7] ; un positionnement plus anté rieur peut mettre cette extré mité en contact avec les aryté noïdes ou les cordes vocales et provoquer une fermeture glottique. Le changement de masque, correspondant à un changement de taille, de modè le ou un recours à l'intubation, n'a é té retrouvé que dans une é tude : Theiler et al ont comparé l'I-Gel TM et le LMA-Suprême TM chez 60 patients pré sentant des critè res d'intubation difficile [8].…”
Section: Discussionunclassified